The effect of hexaconazole on growth performance of Mucuna bracteata / Ahmed Faiz Abd Shukor - Abd Shukor, Ahmed Faiz (Faculty of Plantation and Agrotechnology, 2015)
The main purpose of this study was to determine the growth inhibition of Mucuna bracteata using hexaconazole for controlling its vigorous growth of vines. Different concentrations of Anvil® containing 4.8% hexaconazole as active ingredient were prepared, i.e. 0 for control, 2.5, 5, 7.5 and 10 ml Anvil®/l. Every treatment was replicated five times. The changes of growth of M. bracteata was monitored as changes in the internodal length, internodal diameter, leaf area, relative chlorophyll content and number of leaves at every two weeks for up to eight weeks. This study found that there was significance difference in M. bracteata following application of hexaconazole in terms of the mentioned growth parameters. Hence, the application ofhexaconazole is believed to be able to inhibit excessive growth of M. bracteata.